ANALISIS SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA DI RUMAH SAKIT UMUM DAERAH MUKOMUKO TAHUN 2017 - Nopia Wati; Agus Ramon; Hasan Husin (Avicenna: Jurnal Ilmiah, 2018)
The hospital is a service station that has a variety of complicated labor problems with various risks of occupational diseases and accidents due to work depending on the type of work, so it is obliged to apply the efforts of Occupational Safety and Health of the Hospital. This research aims at analyzing the Occupational Safety and Health Management System at Mukomuko General Hospital. This research was a qualitative descriptive research with in-depth interview design and observation. Informants in this research were Head of Administration, General Department, Head of Medical Services of Mukomuko General Hospital. The research was conducted on July 4 till August 4, 2017 at Mukomuko General Hospital. The results showed that the commitment and policy of Vocational School Number 3 in Mukomuko General Hospital are already exist in the form, provision of funds, facilities and infrastructure that support the implementation of safety and occupational health has been met. Vocational School Number 3 plan in Mukomuko General Hospital has been running well from risk identification to risk management. In addition, workers were also required to follow the SOP in every work. OSH organization has not been established in Mukomuko General Hospital. Management of safety and occupational health RSUD Muko-Muko were located in one level below the director and included in the field of medical services where the core members were from IPSRS Installation and Kesling Installation, Most of the steps of applying Vocational school number 3 have been running well in hospitals Muko-Muko where the hospital has declared the commitment to conduct health and safety counseling to workers, implementation of OSH programs such as provision of PPE, medical examination, and treat sick workers by providing BPJS services. Although the implementation of monitoring and evaluation has not been implemented. It is hoped that the hospital can do evaluation to safety management system and working health periodically can observe the implemented program that has been formulated. Â Keyword: Management, safety, and working health, Mukomuko General Hospital